Processo de inserção laboral: uma visão psicossocial a partir da vivência de jovens da periferia da cidade de Fortaleza - Coelho, Raquel Nascimento (2008)
This work aims to bring an understanding of the psychosocial process of youth labor insertion through the experience of some young people of a periphery community of Fortaleza. We believe that every human phenomenon must be understood related to the socio-historical moment in which it happens, therefore, we started this study delimiting the social context of work where the insertion process happens, bringing some thoughts about the changes in the labor world, which has the precarization and flexibility as one of its main brands, and its consequences for the individuals. Based on this context, we brought our understanding of the condition of being young today, its characteristics and needs. Then we aimed a delimitation of the youth labor insertion process within a broader context of transition to adulthood, in addition to it we brought the increasingly negative position that young people are occupying in the labor market and then we present some alternatives to solve the difficulties faced by them. After this theoretical work, we made a qualitative research with five young people of a periphery community of Fortaleza. We made five semi-directed interviews that were submitted to a semantic content analysis. These contents were organized into four categories, didactically divided to clarify the organization of the data to the reader: meanings assigned to work, experiences in relation to work, insertion trajectories and what has changed?. From the analysis we can say that the labor insertion process is a very important moment in the identity construction of young people and a critical moment in the global experience of these individuals as it makes it possible their social, psychological and economic integration.